Temporomandibular joint osseous morphology in a consecutive sample of ankylosing spondylitis patients. Issue 2 (1st February 1997) - Ramos-Remus, Cesar; Major, Paul; Gomez-Vargas, Amparo; Petrikowski, Grace; Hernandez-Chavez, Abel; Gonzalez-Marin, Enrique; Russell, Anthony S
Abstract : OBJECTIVE: To evaluate temporomandibular joint (TMJ) osseous morphology in a consecutive sample of Mexican patients with ankylosing spondylitis. METHODS: Consecutive patients with a diagnosis of ankylosing spondylitis who attended two secondary care outpatient rheumatology clinics were included in the study. Patients had a rheumatological assessment using a structured questionnaire and examination. Recorded variables included demographic data, disease characteristics, TMJ symptoms, and axial mobility measurements. Hypocycloidal tomography of the TMJ was obtained on all subjects. Radiographic variables included condyle position, superior joint space, range of movement, condylar osseous changes, and temporal osseous changes. Patients also underwent standard cervical spine radiography. A control group of normal people without either TMJ symptoms or systemic rheumatic disease was obtained. RESULTS: 65 subjects were studied (65 right sided and 63 left sided tomograms). The control group consisted of 22 individuals. Both groups were similar in age [33 (SD 11) v 34 (9) years, P = 0.8]. Patients with ankylosing spondylitis had more variability in TMJ mobility than controls (P < 0.05) and showed increased frequency of condylar erosions (P < 0.01), flattening (P < 0.01), sclerosis (P < 0.01), and temporal flattening (P < 0.01). Condylar erosions were associated with longer duration of ankylosing spondylitis (P < 0.05), neck complaints (P < 0.05), and atlantoaxial subluxation (P < 0.05). CONCLUSIONS: TMJ involvement is frequent in this population of patients with ankylosing spondylitis and is associated with variables that suggest more severe disease.